Praktik Nilai-Nilai Religius sebagai Upaya Meminimalisir Tindak Kenakalan Peserta Didik di SMA Negeri 1 Ngoro - Nando Bramastha; Rr. Nanik Setyowati (Kajian Moral dan Kewarganegaraan, 2023)
This study describes the practice of religious values ​​to minimize student delinquency at SMA Negeri 1 Ngoro. This study aims to (1) describe the practice of religious values ​​as an effort to minimize student delinquency at SMAN 1 Ngoro, (2) identify any obstacles in the practice of religious values ​​as an effort to minimize student delinquency in SMAN 1 Ngoro. This research method uses a qualitative approach, with a descriptive research design. Data collection techniques used are observation, interviews and documentation. The theory used in this research is Thomas Lickona's character education theory. The results showed SMA Negeri 1 Ngoro had practiced religious character education through daily activities such as the obligation to pray dhuha, morning apples and youth prayer activities. The first obstacle that arises in the practice of religious values ​​is the lack of awareness from students so that there are still many who underestimate the activities provided. Second, the number of students who came late so they could not take part in the activities with the most reason being that the departure time was too early. Third, the obstacles experienced are in the process of maintaining the activities that have been given, because with the response from students who are few, SMA Negeri 1 Ngoro often changes concepts in implementing religious character education. Keywords: Religious Character Education, Student Delinquency